2017
DOI: 10.3747/co.24.3562
|View full text |Cite
|
Sign up to set email alerts
|

Real-Life Treatment of Metastatic Colorectal Cancer with Regorafenib: A Single-Centre Review

Abstract: Background Various tyrosine kinase signalling pathways affect the development and progression of colorectal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 5 publications
(4 reference statements)
2
10
0
Order By: Relevance
“…Because of our small sample, further studies involving more patients are needed to confirm this information. life data, regorafenib was associated with a survival similar to that reported in the randomized controlled trials (7)(8)(9)(10)(11).…”
Section: Discussionsupporting
confidence: 74%
“…Because of our small sample, further studies involving more patients are needed to confirm this information. life data, regorafenib was associated with a survival similar to that reported in the randomized controlled trials (7)(8)(9)(10)(11).…”
Section: Discussionsupporting
confidence: 74%
“…A Japanese retrospective study demonstrated that there was no clear reduction in clinical efficacy when the regorafenib dose was modified to an intensity of 59% compared with the standard dose. 39 The other study that analyzed data from patients with mCRC used different regorafenib starting doses: 54% of patients received 160 mg, 40% received 120 mg, and 6% received 80 mg. 40 Those results indicated that various starting doses had no association with survival in univariate or multivariate analysis. Recently presented data from the Regorafenib Dose Optimization Study (ReDOS) demonstrated that a strategy with weekly dose escalation of regorafenib from 80 to 160 mg daily was superior to the standard dose of 160 mg daily in patients with mCRC.…”
Section: Discussionmentioning
confidence: 96%
“…This approach differs from tumor response assessments in clinical trials that are performed at regular intervals. However, this real-world best tumor response assessment approach has been used in other observational settings 1,7,8 . OS was defined as the time between index date and death.…”
Section: Study Design and Study Populationmentioning
confidence: 99%